Pelindungan Hak Pilih Penyandang Disabilitas Mental dalam Pendekatan Rangkaian Proses Pasca Putusan Mahkamah Konstitusi Nomor 135/PUU-VIII/2015 - Fajri Nursyamsi; Muhammad Nur Ramadhan (Jurnal Adhyasta Pemilu, 2020)
The Constitutional Court Decision Number 135 / PUU-XIII / 2015 stated that the requirement for "not being mentally / memory disturbed" to be registered as a voter in Law Number 8 of 2015 is unconstitutional. The decision opens a new perspective on the protection of suffrage for persons with mental disabilities, and acknowledges that mental / memory impairment conditions are not the same between one person and another. The decision is in accordance with the development of thoughts on the legal capacity of persons with disabilities using a continuum approach, which recognizing that everyone is a legal subject, but practically it is necessary to look at the person's ability to exercise their rights, especially in decision making. The Constitutional Court decision has been applied in various regulations related to elections, which cannot be separated from the efforts of disabled people organizations to implement it. However, the changes are still at the administrative level, have not resulted in a change in perspective on the recognition of the legal capacity of persons with mental disabilities. In practice, there are still cases of persons with mental disabilities who were not registered as voters so that they are forced to be unable to exercise their voting rights. Based on this explanation, it is important to analyze how the legal capacity approach for persons with mental disabilities is used in the Constitutional Court decisions Number 135 / PUU-XIII / 2015, and how this approach should be applied to ensure the protection of the suffrage rights of persons with disabilities. This legal research was conducted using a qualitative approach, using primary sources of law in the form of statutory regulations and other forms of policy, as well as secondary sources of law in the form of literature and other valid and relevant information. This study presents a discussion of the suffrage rights of persons with mental disabilities using a continuum approach that has not been discussed in previous studies, so that it is expected to be able to sharpen the implementation.